A review on recent developments in the adsorption of surfactants from wastewater - Siyal, A.A. (Academic Press, 2020)
The pollution of the world's water resources is a growing issue which requires remediation. Surfactants used in many domestic and industrial applications are one of the emerging contaminants that require immediate attention. Treating water contaminated with surfactants using adsorption provides better performance when compared to other techniques. A variety of materials have been developed for adsorbing surfactants. Activated carbon is the most suitable adsorbent for removing surfactants but is expensive to synthesize and difficult to regenerate. Therefore, a variety of new adsorbents such as zeolites, nanomaterials, resins, biomaterials and clays have been developed as alternatives. The developed adsorbents are promising but considerable research is still required to develop highly efficient, economical, environment friendly and sustainable adsorbents to replace activated carbon. This paper critically reviews the characteristics of adsorbents, the performance of adsorbents, kinetics, isotherms and thermodynamics, mechanisms of adsorption, regeneration of adsorbents and future perspectives in the adsorption of surfactants. Developing novel adsorbents, testing adsorbents in real wastewaters and recycling the adsorbents are required in future studies in the removal of surfactants. Â© 2019 Elsevier Ltd